Olympic or Sacred? The Controversy over the Flame at the Inaugural 1951 Pan-American Games and Its Aftermath. Issue 4 (24th March 2019) - Torres, Cesar R.
Abstract: In 1951, Buenos Aires hosted the inaugural Pan-American Games. On February 25 of that year, a Greek athlete carried a flame flown specially from his country onto the stadium where the event's opening ceremonies took place and lit the cauldron. The uncertain character of the Greek flame transported to Buenos Aires alarmed many in Olympic circles. Confused and concerned, the International Olympic Committee (IOC) investigated the matter, which led to a rapid succession of policy changes seeking to regulate the use of flames in regional games. The flame flown from Greece to Buenos Aires for the 1951 Pan-American Games sparked an intense debate about the status of the Olympic flame. The IOC's recognition of the power of the Olympic flame ritual and its preoccupation with protecting it along with other Olympic symbols and terminology reveal the contours of the organization's ideology in this era and its relations with associated entities. The flame debate also illuminates the push by Pan-American Games' officials for autonomy. Clearly, Olympic officials recognized early in the 1950s that the globalization of the Olympic flame ritual required regulation if the IOC was to ensure control of this and its other symbolic resources.